Armenian National Supercomputing Center: Bridging Science and Technology through High-Performance Computing - Mirzoyan, A.; Sahakyan, V.; Shoukourian, Yu; Astsatryan, H. V. (Physics of particles and nuclei, 2025)
Supercomputing allows researchers, industry, and stakeholders to use computational models to simulate challenging or impossible conditions to replicate and measure in a laboratory setting. National and regional supercomputing centers provide the computational power to tackle complex problems across various disciplines that require new programming paradigms and runtimes. The paper provides an overview of the Aznavour supercomputer, a national digital infrastructure leveraging existing high-performance computing Big Data infrastructures. Its establishment accelerates scientific discovery and positions Armenia as a critical player in the global tech ecosystem. Aznavour opens up new opportunities for research and development, allowing scientists and engineers to solve problems previously considered impossible and advancing future innovations and technologies. The paper presents the prerequisites for establishing the supercomputing center, tracing its evolution from cluster computing to cloud computing. It also delves into the Aznavour supercomputer’s architecture, detailing its software and hardware components, and highlights the various scientific and engineering communities driving demand for these high-performance computing resources.